2016
DOI: 10.3390/rs9010018
|View full text |Cite
|
Sign up to set email alerts
|

Potential of ALOS2 and NDVI to Estimate Forest Above-Ground Biomass, and Comparison with Lidar-Derived Estimates

Abstract: Remote sensing supports carbon estimation, allowing the upscaling of field measurements to large extents. Lidar is considered the premier instrument to estimate above ground biomass, but data are expensive and collected on-demand, with limited spatial and temporal coverage. The previous JERS and ALOS SAR satellites data were extensively employed to model forest biomass, with literature suggesting signal saturation at low-moderate biomass values, and an influence of plot size on estimates accuracy. The ALOS2 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 57 publications
(71 reference statements)
2
27
0
Order By: Relevance
“…Among available variables, perplexity, Shannon index, and entropy were found most correlated with the referenced aboveground biomass with R 2 0.67, 0.67, and 0.66, respectively; these results are in line with the results obtained in published literature [31][32][33][34][35][36]. Detailed regression results are shown in Table 3.…”
Section: Resultssupporting
confidence: 87%
“…Among available variables, perplexity, Shannon index, and entropy were found most correlated with the referenced aboveground biomass with R 2 0.67, 0.67, and 0.66, respectively; these results are in line with the results obtained in published literature [31][32][33][34][35][36]. Detailed regression results are shown in Table 3.…”
Section: Resultssupporting
confidence: 87%
“…For instance, the ratio vegetation index (RVI) is effective for retrieval of the mangrove structure [48]. The normalized difference vegetation index (NDVI) has been widely used for mangrove AGB as it is strongly correlated with mangrove biophysical parameters [49]. Further, enhanced vegetation index-2 (EVI-2) is relatively sensitive to mangrove AGB [50,51].…”
Section: Image Transformation Of the S-2 Multispectral And Alos-2 Palmentioning
confidence: 99%
“…For example, reported studies suggested that improved spatial resolution from the Sentinel series helped to reduce the uncertainty, and improved the accuracy of AGB mapping at finer scale [52,53]. Promising results demonstrated that texture measurement of SAR data with higher spatial resolution could improve biomass estimation [54,55]. However, uncertainties in implementing the texture measurement for biomass estimation were reported, due to the selection of window size [56,57].…”
Section: Satellite Data Pre-processing and Derived Variablesmentioning
confidence: 99%